A performance recovery coefficient for thermal-hydraulic evaluation of recuperator in supercritical carbon dioxide Brayton cycle. (15th March 2022) - Li, X.L.; Tang, G.H.; Fan, Y.H.; Yang, D.L.
Highlights: An integrated model of Brayton cycle with recuperator design is developed. The effects of recuperator design parameters on cycle efficiency are discussed. The existing criteria are not sufficient for performance evaluation of recuperators. A new criterion of performance recovery coefficient is proposed. The new criterion is general to evaluate performance of recuperator in Brayton cycle. Abstract: Recuperator is an important component in supercritical carbon dioxide Brayton cycle. However, open literature mainly focused on the performance of recuperator in component scale but the effect of its thermal–hydraulic performance on the cycle efficiency was seldom concerned. Besides, to be more convenient in practical applications, a criterion for thermal–hydraulic evaluation of recuperators in supercritical carbon dioxide Brayton cycle is needed to avoid the coupling analysis of recuperator design and cycle design. In the present study, an integrated model is developed by combining the supercritical carbon dioxide Brayton cycle with the recuperator of a printed circuit heat exchanger. Based on the integrated model, the effects of design parameters of recuperator on the cycle performance are discussed. It is shown that ultra-large Reynolds number and effectiveness fail to improve the cycle efficiency and are not recommended due to the caused large pressure drop. The effects of conventional performance evaluation criteria and the ratio of heat transfer rate to pressure drop on cycle efficiency are also examined. It is indicated that the existing criteria are not sufficient to evaluate the effect of recuperator channel configuration on cycle efficiency. The performance recovery coefficient with value between 0 and 1 is finally proposed and validated to be an effective and convenient criterion as well as straightforward to various cycle layouts with other types of recuperators.